Digital Leadership in Islamic Education: Driving Instructional Media Innovation at MA Al-Islam Surakarta - Habibi Fadzlurrahman; Triono Ali Mustofa (FKIP - Universitas Riau, 2026)
The development of digital technology has driven major changes in learning practices in schools, including in Islamic education. This study aims to analyze the role of school leadership in encouraging the use of digital media as a learning innovation at MA Al-Islam Surakarta, as well as to examine the strategies used to manage the process of integrating technology into teaching and learning activities. This study uses a qualitative approach with field research. Data were collected through in-depth interviews with the principal, teachers, and students, as well as direct observation of digital media-based learning practices in the classroom. Data were analyzed using reduction, presentation, and conclusion-drawing techniques, with data validity maintained through triangulation of sources and methods. The results of the study show that the principal acts as an agent of change who not only sets policies but also builds a digital culture through the provision of infrastructure, continuous training, teacher mentoring, and strengthening collaboration. Communicative, participatory, and adaptive leadership strategies have proven to be able to encourage teachers and students to use digital media more creatively.